Linking Labour Division within Families, Work–Life Conflict and Family Policy - Szalma, Ivett (2020)
This thematic issue aims to shed light on the various ways of linking division of labour within families, work–life conflict and family policy in Europe. This editorial briefly introduces key concepts and provides a general overview of the published articles.